Pengaruh Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Guru Di SMK Islam Paniis - Anisa Ramdani; Rita Tri Yulistia; Nita Fauziah Oktaviani (Journal of Management and Creative Business, 2023)
Teacher performance is the result, progress, and work performance of the teacher in carrying out learning and evaluating learning outcomes, conducting guidance and training on students, as well as their commitment to carrying out tasks. This study aims to determine the simultaneous effect of leadership and work discipline on teacher performance as well as the partial effect of leadership on teacher performance and the partial effect of work discipline on teacher performance. The population used in this research was Paniis Islamic Vocational School teachers. The method used in this study is a quantitative method through the causality method with a survey approach. The sampling technique is saturated sampling technique, the number of samples taken is 41 people. The data analysis technique uses multiple linear regression with the help of SPSS version 25. Based on the results of the study it is concluded that leadership and work discipline simultaneously have a significant effect on teacher performance. Partially, leadership has a significant effect on teacher performance. Partially, work discipline has no significant effect on teacher performance.